Antimalarial Activity of Certain Sudanese Medicinal Plants Used in Folk –Medicine - M. Ahmed, EL-Hadi; S. Khalid, Hassan; G. Mohammed, Yousif G. Mohammed (المجلة الزراعية; مجلد 3 عدد 1 (2005), 2021)
Ten indigenous plants of common use in Sudanese folk-medicine, vitro for antimalarial activity against Plasmoclium were examined in falciparum , the major human malaria parasite. All plant samples displayed various antimalarial activity. Three plant extracts caused 100% inhibition of the parasite growth at a concentration ≤ 500 g/ml. The most active extracts that produced 100% inhibition of the parasite growth at a concentration ≤ 50 g/ml were obtained from the seeds of Nigella sativa and the whole plant of Aristolochia bracteolata. These two plants were phytochemically screened for their active constituents and both showed the presence of sterols, alkaloids and tannins.